Identifikasi Potensi Asap Akibat Kebakaran Hutan terhadap Rencana Pembangunan Tapak PLTN Kabupaten Bengkayang: Identification of Potential Smoke Due to Forest Fires on the Bengkayang Regency Nuclear Power Plant Site Development Plan - Dian Rahayu Jati; Yulisa Fitrianingsih; Kiki Prio Utomo; Aini Sulastri (Jurnal Teknologi Lingkungan, 2023)
Land and forest fires in West Kalimantan have been going on for a long time and in recent years it has gotten  worse with the increasing number of hotspots which has reduced visibility due to haze. This decrease in visibility reaches a considerable distance from the source of the forest fire. This condition has an impact on health problems, transportation, and population density. Bengkayang Regency was chosen as the location for the prototype site for the West Kalimantan nuclear power plant prototype which is planned to be built in 2024. The location that has been determined is Gosong Beach, Sungai Raya Islands District, with coordinates 108o 051'30” W – 108o 05' 23'' East and 00o 43 ' 50'' N – 00o 41' 15” South. This study aims to predict the distribution of PM10 due to forest fires at prospective site locations within a radius of 25 km based on hotspot point data during 2010–2020 using The American Meteorology Society Environmental Protection Agency Regulatory Model (AERMOD) method. The results showed that the number of hotspots around the location was 2,873 points in a period of 10 years. Four locations experience repeated events throughout the year within a radius of 25 km with the closest point as far as 5.34 km from the site location. Based on AERMOD modeling using 2020 meteorological data, the fastest possible distribution directly from the 4 points follows the south to west direction and does not go to the site location, but the closest distance to the site is 3.08 km.ABSTRAK Kebakaran lahan maupun hutan di Kalimantan Barat telah terjadi sejak lama dan beberapa tahun terakhir semakin parah dengan meningkatnya jumlah titik hotspot yang berdampak pada turunnya jarak pandang akibat kabut asap. Penurunan jarak pandang ini sampai pada jarak yang cukup jauh dari sumber terjadinya kebakaran hutan. Kondisi ini berdampak pada masalah kesehatan, transportasi, dan mobilitas penduduk. Kabupaten Bengkayang dipilih sebagai lokasi calon tapak prototipe Pembangkit Listrik Tenaga Nuklir (PLTN) Kalimantan Barat yang rencananya akan dibangun pada tahun 2024. Lokasi yang telah ditentukan adalah Pantai Gosong Kecamatan Sungai Raya Kepulauan, dengan koordinat 108o 051’30” BB – 108o 05’ 23’’ BT dan 00o 43’ 50’’ LU – 00 41’ 15”LS. Penelitian ini bertujuan untuk memprediksi sebaran PM10 akibat kebakaran hutan pada calon lokasi tapak pada radius 25 km berdasarkan data titik hotspot sepanjang tahun 2010-2020 dengan menggunakan metode The American Meteorology Society Environmental Protection Agency Regulatory Model (AERMOD). Hasil penelitian menunjukkan jumlah titik hotspot yang terdapat pada sekitar lokasi sebanyak 2.873 titik dalam kurun sepuluh tahun. Terdapat 4 lokasi yang mengalami kejadian yang berulang sepanjang tahun dalam radius 25 km dengan titik terdekat sejauh 5,34 km dari lokasi tapak. Berdasarkan pemodelan AERMOD yang menggunakan data meteorologi tahun 2020, arah sebaran asap dari 4 titik tersebut mengikuti arah Selatan menuju Barat dan tidak menuju lokasi tapak, akan tetapi panjang sebaran terdekat dengan tapak adalah sejauh 3,08 km dari rencana lokasi tapak